KETELUSURAN GENETIK KETURUNAN KELAPA SAWIT (Elaeis guineensis Jacq.) MENGGUNAKAN SIMPLE SEQUENCE REPEAT (SSR) - Rokhana Faizah; Sri Wening; Yurna Yenni; Sujadi Sujadi (Jurnal Penelitian Kelapa Sawit, 2016)
Progenies traceability status becomes an important activity in the oil palm breeding program, especially to obtain propriety of individual and progenies population with their parents. This study is concerned to analyze genetic traceability based on pattern and allele size of their parent using Simple Sequence Repeat (SSR) markers. There were 90 palms from 7 progenies populations in the AD02S, AD03S Adolina and MA22S Marihat Estate PT. Perkebunan Nusantara IV used in this research. Leaf and pollen samples were used to get genomic DNA. Then, DNA genomic was amplified using multiplexing method of 8 SSR markers and fluorescence labels of 6-FAM, HEX, and NED. Fragment analysis and extracted genotype data was obtained using Gene Marker® versi 2.4.0 Soft Genetics® LLC program. Genetic traceability analysis was based on alelle segregation pattern of Mendelian Law. The results described inappropriate alleles 4 individuals from 3 progenies (N, P, and S). Those individuals were palmrow of 22-30 in the AD02S; 29-27 in the MA22S; 9-22 and 9-28 in the AD02S. Other 4 progenies showed an appropriate segregation of genotype with their parents, which are crosses number of M, Q, R, and O.